A Study on Standard of Buffalo Meat Hygiene in Dharan - Adhikari, Bhaskar Mani; Subedi, Rajendra Prasad; Subba, Dilip (Journal of Food Science and Technology Nepal, 2014)
Hygiene standard of buffalo meat in Dharan was assessed by microbiological analyses and field survey method. Ten samples of buffalo meat, knives, chopping board and hands of butchers were examined for total plate count (TPC), total coliforms, E. coli, Staphylococcus aureus, Salmonella and Shigella. Average of TPC, Coliforms, E. coli and S. aureus counts in meat were 3.59×107, 2.06×104, 1.69×103 and 9.67×103 cfu/g respectively. Salmonella was detected in 80% samples and all samples were Shigella positive. The average TPC count of chopping board, knives and hands were found to be 3.15×104, 3.47×103 and 2.01×104 cfu/ cm2 respectively. The average Coliform, E. coli and S. aureus counts of chopping board were found to be 1.11×103, 9.8× 101 and 6.2×102 cfu/cm2. The average Coliform, E. coli and S. aureus counts of knives were found to be 1.31×103, 1.66×102 and 2.83×102 cfu/cm2. The average Coliform, E. coli and S. aureus counts of the palms of butchers were found to be 1.95×103, 1.66×102 and 1.77×102 cfu/cm2. Two chopping boards, three knives and three hands were found Salmonella free. Five chopping boards, three knives and two hands were detected for Shigella. The field survey of 31 meat shops showed that the hygiene condition of meat sold in Dharan was found unsatisfactory. DOI: http://dx.doi.org/10.3126/jfstn.v7i0.10617 J. Food Sci. Technol. Nepal, Vol. 7 (99-101), 2012